A Survey of Computer Education Courses in Canadian Faculties of Education - Collis, Betty; Muir, Walter (Canadian Journal of Higher Education, 1986)
Paralleling the rapid entry of microcomputers into the elementary and secondary schools of Canada has been the development of a broad range of credit courses, within faculties of education, designed to train teachers in the application of computer technology to teaching and learning. This survey of computer education courses and programs in Canadian faculties of education was conducted in February 1985, in order to provide baseline data for a continuing review of the nature and impact of these courses. The results of the survey confirm that the response of education faculties has been quite dramatic, with a total of 260 undergraduate and 85 graduate courses now being offered. However, categoriza- tion of the courses shows considerable diversity in both content and sequence. Further, there is no consistency among the various institutions in their requirements for computer-related experiences prior to teacher certification.